Polestar refined: Business ethics and political economy - Danley, John R. (Journal of business ethics, 1991)
Although Friedman's ‘The Social Responsibility of Business is to Increase Profits’ is widely read, the central argument is rarely identified. Stone's discussion of Friedman in Where the Law Ends, is often used as a companion piece. Stone claims that the most important argument in Friedman is the Polestar argument but never succeeds in explaining what it is. This paper shows that Friedman's position must be read in the context of his theory of political economy, and that at least four distinct utilitarian arguments are required to account for his views. Specifically, Friedman relies upon what I describe as Realistic Rule Utilitarianism in which utility is understood in terms of actual preferences. The weaknesses of this theory are then explained.